Peningkatan Sanitasi Sekolah Lewat Kegiatan Lomba Toilet Bersih antar Sekolah di Desa Lobu Mandiri Parigi - Christine, Christine; Agustiany, Dessy (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Basic sanitation and enhanced healthy behavior will immediately lower the number of illnesses caused by poor sanitation. People suffer from a variety of ailments as a result of poor sanitation. Pupils spend most of their time at school, thus providing good sanitary facilities is vital for their health. This community service activity aimed to raise public awareness, particularly among school members, about the importance of sanitation facilities in schools in improving the health of school members to avoid disease infection, which can reduce attendance and learning achievement in schools at Lobu Mandiri village, Parigi Moutong. A clean toilet competition among four schools was held as the method on 21 February – 4 March 2022 in Lobu Mandiri Village. As a result of the competition, the condition of the toilets in the participating schools was improved. The cleaner toilets and the availability of sufficient water made students feel more comfortable using them. Another method required to improve sanitation is health education for school members and the children's parents.